Developing Islamic Banking and Financing System : SIPKe-i - Abd Jalil, Borham; Awang, Mohd Ghani; Zubir, Sharifah Intan Safina Syed (2010)
SiPKe-i or Islamic Banking and Financing Management System is a project on building a web-based management system that can be used by professional or semi-professional banking representative as a reference or learning tools that may help in decision making situation which required expertise in Shariah banking and financing concept. This system will also become a platform that enabled Islamic banking and financing activities to be done in the correct procedure. The information provided in this system will mainly focused on the procedure, concept and the main principle of the Islamic banking and financing based on the Shariah law to help the understanding of the target user and consumer. Furthermore the system are web-based thus this system can be available through the internet by any user thus this will be easily accessible for user who have internet connection available.